Improvement of Comfort in Suspension Seats with a Pneumatic Negative Stiffness System - Eduardo Palomares; Angel L. Morales; Antonio J. Nieto; Jose M. Chicharro; Publio Pintado (Actuators, 2020)
This paper presents a Negative Stiffness System (NSS) for vibration isolation and comfort improvement of vehicle seats, which enhances the performance of optimized traditional passive seat suspensions. The NSS is based on a set of two Pneumatic Linear Actuators (PLAs) added to a seat supported by a pneumatic spring. One end of each PLA is joined to the seat while the other end is joined to the vehicle frame. In static conditions, the PLAs remain horizontal, whereas in dynamic conditions, their vertical forces work against the pneumatic spring, reducing the overall dynamic stiffness and improving passenger comfort. The paper presents a stability analysis of the highly nonlinear dynamic system, as well as the numerical determination of the optimum PLA pressure for a given passenger mass that maximises comfort without instabilities. Finally, the performance of the proposed NSS is compared to that of a traditionally optimized passive seat suspension via simulations of an eight-degree-of-freedom vehicle model traversing several road profiles and speed bumps. Comfort improvements between <semantics>10%</semantics> and <semantics>35%</semantics> are found in all tests considered.